Plasma von Willebrand factor, thrombosis, and the endothelium: The first 30 years - Blann, Andrew D. (Thrombosis and Haemostasis, 2006)
“It is quite useless to argue the questions concerning the development of intimal scleroses if we study and discuss the late stages of the disease alone. If we wish to gain insight into the complex question of arterio-sclerosis we must attempt to follow the lesion from its earliest beginning” (Klotz and Manning, J Path Bact 1911: 16; 211–20).Over thirty years ago Boneu and colleagues publisheda report of raised levels of plasma vonWillebrand factor (vWf) in patients with arteritis, diabetes and sepsis. They concluded that raised levels of this molecule indicate endothelial damage, and may possibly be a contributory factor in thrombosis in arterial disease. The former aspect of this conclusion is now accepted, and numerous studies on the risk factors for atherosclerosis provide mechanisms for this damage. Other studies have demonstrated raised levels in cancer and in connective tissue disease. Numerous long-term follow-up studies have also demonstrated that increased vWf predicts major cardiovascular end points. However, the link between these studies, and the latter aspect of Boneu’s conclusion, that raised vWf contributes to thrombosis is,although attractive, nevertheless unproven. Despite this, vWf remains the most important plasma marker of endothelial damage/dysfunction and as such attracts clinical attention.
Keywords: Endothelium; vonWillebrand factor; thrombosis; atherosclerosis